Characterization and Separation of Platinum-Based Antineoplastic Drugs by Zwitterionic Hydrophilic Interaction Liquid Chromatography (HILIC)–Tandem Mass Spectrometry, and Its Application in Surface Wipe Sampling - Stefano Dugheri; Nicola Mucci; Enrico Mini; Donato Squillaci; Giorgio Marrubini; Gianluca Bartolucci; Elisabetta Bucaletti; Giovanni Cappelli; Lucia Trevisani; Giulio Arcangeli (Separations, 2021)
Platinum-based antineoplastic drugs (PtADs) are among the most important and used families of chemotherapy drugs, which, even showing severe side effects and being hindered by drug resistance, are not likely to be replaced clinically any time soon. The growing interest in the occupational health community in antineoplastic drug (AD) surface contamination requires the development of increasingly fast and easy high-throughput monitoring methods, even considering the lack of harmonized legally binding regulation criteria. Thus, a wipe sampling method together with zwitterionic hydrophilic interaction liquid chromatography (HILIC-Z)–tandem mass spectrometry (MS/MS) analysis was developed for the simultaneous evaluation of oxaliplatin, cisplatin, and carboplatin surface contaminations. A design of experiments approach was used to optimize the chromatographic conditions. Limits of quantification ranging from 2 to 5 ng/mL were obtained from interday and intraday repetitions for oxaliplatin and carboplatin, and between 170 and 240 ng/mL for cisplatin. The wipe desorption procedure is equivalent to other AD sampling methods, enabling a fast sample preparation, with an LC-MS/MS analysis time of less than 7 min.